Task variation as a crucial point in technique training of alpine ski racers - Kröll, J.; Birkbauer, J.; Müller, E. (14th annual Congress of the European College of Sport Science, Oslo/Norway, June 24-27, 2009, Book of Abstracts, 2009)
Variability, which traditionally (and from traditional motor learning perspectives) has been considered to be noise and detrimental to normal function, has more recently been considered to be an essential element to offer flexibility in adapting to perturbations (Hamill et al 1999). Therefore a crucial point of modern methods in motor learning is a high degree of task variations. According to Bernstein (1967) our central nervous system has a compensation function between necessary movement forces and reactive phenomena (gravitation, inertia, forces stored in muscle-tendon-unit). Altering these reactive phenomena requires different neuromuscular patterns for an appropriate movement outcome. In Alpine ski racing we have movements which have constantly cyclic components (turn by turn), but, compared to other cyclic movements (e.g. running), external circumstances which alter reactive phenomena in a distinct amount (e.g. snow conditions). With regard to technical training of elite alpine skiers our aim is to find task variations which additionally alter those reactive phenomena, but not exceed the solution space for ski racing. Therefore the interpolation ability to adequately adapt to new situations should be improved. To fulfill these requirements, two specific training devices were developed and evaluated by comparing some task variations to normal ski racing. The first device is a ´see-saw´ based plate between the binding and the ski (Sensowip, Kröll et al 2006). The plate can be cushioned by springs or fixed with an inclination in sagittal plane. The second device is a system based on elastic cords fastened between joints acting as constraints to increase the degree of freedom and consequently the alteration of reactive phenomena (Tendybelt). This device is not exclusively designed for alpine skiing as studies on running and volleyball were performed recently with similar theoretical background (e.g. Haudum et al 2008). In the current presentation, kinetic variations of several settings (3 SensoWip tasks; 3 Tendybelt tasks) compared to the normal situation (case studies) and the influence on runtimes during a training session (n=7) will be presented. Strong effects in all six tasks were found for the force distribution in sagittal plane (up to 25%, eta2=.74), while the overall force distribution between inside and outside was only marginally influenced (up to 3%, eta2=.09). The influence on runtimes was in 4 tasks significant but in all cases lower than 6%. It can be concluded that the use of the two devices alters substantially the reactive phenomena, while the solution space for ski racing technique is not exceeded. Hence, the devices generate movement variations similar to that recommended for modern technical training.